(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is known that any three - Regulargraph, planar and connected, and all the faces in it are pentagonal or hexagonal, thenthe number of pentagons in it is double the number of hexagonal edges, i.e. 12. [6]. The purpose of this paper is to prove the following: Given ans-regular graph,planar and connected, and all the faces in it contain only (l)or (l+1)edges, also